Incidence and predisposing factors of chalazion - Alsammahi, Alaa; Aljohani, Ziyad; Jaad, Nafisah; Abu Daia, Omamah; Aldayhum, Majed; Almutairi, Mohammed; Basendwah, Mohammad; Alzahrani, Reham; Alturki, Muna (International Journal Of Community Medicine And Public Health, 2018)
Chalazion is one of the most common eyelid masses seen by ophthalmologists in outpatient clinics. It presents with slowly growing painless cystic lesion affecting eyelids. Chalazion arises due to obstruction of the meibomian gland ducts leading to retained secretion. The exact incidence of chalazion is variable among the studies and it differs depending on certain predisposing factors. Many factors ae known to predispose to chalazion formation including hormonal changes during puberty and pregnancy, viral and bacterial infection, rosacea, exposure to air pollutants, poor eyelid hygiene, chronic blepharitis, seborrheic dermatitis, eyelid trauma, immune deficiency states, eyelid trauma, hyperlipidemia, tuberculosis, and leishmaniasis. This article will review these factors as well as the incidence of chalazion.